Self-deception unmasked - Mele, Alfred R., 1951- (Princeton monographs in philosophy., 2001)
Self-deception raises complex questions about the nature of belief and the structure of the human mind. In this book, Alfred Mele addresses four of the most critical of these questions: What is it to deceive oneself? How do we deceive ourselves? Why do we deceive ourselves? Is self-deception really possible? Drawing on empirical research on everyday reasoning and biases, Mele takes issue with commonplace attempts to equate the processes of self-deception with those of stereotypical interpersonal deception. Such attempts, he demonstrates, are fundamentally misguided, particularly in the assumption that self-deception is intentional. In their place, Mele proposes an account of the motivational causes of biased beliefs. At the heart of this theory is an appreciation of how emotion and motivation may, without our knowing it, bias our assessment of evidence for beliefs. Highlighting motivation and emotion, Mele develops a pair of approaches for explaining the two forms of self-deception: the "straight" form, in which we believe what we want to be true, and the "twisted" form, in which we believe what we wish to be false. --From publisher's description